Real-life experience with hydroxyurea in sickle cell disease: A multicenter study in a cohort of patients with heterogeneous descent - Piel,FBJ; Rigano,P; De,Francesci L; Sainati,L; Piga,A; Cappellini,MD; Fidone,C; Masera,N; Palazzi,G; Gianesin,B; Forni,GL (Blood Cells, Molecules and Diseases, 2017)
We conducted the first nation-wide cohort study of sickle cell disease (SCD) in Italy, a Southern European country exposed to intense recent flux migration from endemic areas for SCD. We evaluate the impact of hydroxyurea on a total of 652 pediatric and adult patients from 33 Reference Centers for SCD (mean age 24.5 ± 15 years, 51.4% males). Hydroxyurea median treatment duration was 7 years (range: < 1 year to 29 years) at a mean therapeutic dose of 18 ± 4.7 mg/kg/day. Hydroxyurea was associated with a significant increase in mean total and fetal hemoglobin and a significant decrease in mean hemoglobin S, white blood and platelet counts, and lactate dehydrogenase levels. Hydroxyurea was associated with a significant reduction in the incidence of acute chest syndrome (− 29.3%, p < 0.001), vaso-occlusive crisis (− 34.1%, p < 0.001), hospitalization (− 53.2%, p < 0.001), and bone necrosis (− 6.9%, p < 0.001). New silent cerebral infarction (SCI) occurred during treatment (+ 42.4%, p < 0.001) but not stroke (+ 0.5%, p = 0.572). These observations were generally consistent upon stratification for age, descent (Caucasian or African), genotype (βS/βS, βS/β0 or βS/β+) and duration of treatment (< or ≥ 10 years). There were no new safety concerns observed compared to those commonly reported in the literature. Our study, conducted on a large population of patients with different descent and compound state supports the benefits of hydroxyurea therapy as a treatment option. Registered at clinical trials.gov (NCT02709681).